1998
DOI: 10.1007/bf03012906
|View full text |Cite
|
Sign up to set email alerts
|

SIADH following laparoscopic cholecystectomy

Abstract: Clinical Report SIADH following laparoscopic cholecystectomyPurpose: To present an unusual case of inappropriate antidiuretic hormone secretion syndrome a~er a minor surgical procedure in a healthy patient.Clinical features: A 71-yr-old woman underwent uneventful laparoscopic cholecystectomy for gallstones under general anaesthesia. Fifty-two hours post operatively she began convulsing and was found to have a serum sodium concentration as low as I 12 mmol'L -~. Serum osmolality, urinary sodium concentration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…Miller et al reported findings of a large retrospective study of idiopathic hyponatremia in an ambulatory geriatric population which support the hypothesis that aging is a risk factor for the development of SIADH-like hyponatremia in a subset of older patients without any apparent underlying etiology (1 1). Corn forth reported that an elderly patient, with a preoperative serum sodium concentration at the lower end of the normal range, had presented SIADHafter laparoscopic cholecystectomy (9). They believed it reasonable to recognize that their patient might be within a subset of elderly people at the risk of developing SIADHwithout other risk factors described by Miller et al ( case, the possibility of the restriction having been insufficient cannot be ruled out.…”
Section: Discussionmentioning
confidence: 97%
“…Miller et al reported findings of a large retrospective study of idiopathic hyponatremia in an ambulatory geriatric population which support the hypothesis that aging is a risk factor for the development of SIADH-like hyponatremia in a subset of older patients without any apparent underlying etiology (1 1). Corn forth reported that an elderly patient, with a preoperative serum sodium concentration at the lower end of the normal range, had presented SIADHafter laparoscopic cholecystectomy (9). They believed it reasonable to recognize that their patient might be within a subset of elderly people at the risk of developing SIADHwithout other risk factors described by Miller et al ( case, the possibility of the restriction having been insufficient cannot be ruled out.…”
Section: Discussionmentioning
confidence: 97%
“…Miller et al [27] reported findings of a large study of apparent idiopathic hyponatremia in an ambulatory geriatric population, which supports the hypothesis that aging is a risk factor for the development of SIADH-like hyponatremia in patients with no other apparent underlying etiology. Some authors have reported that elderly patients with a preoperative serum sodium concentration at the lower end of the normal range developed SIADH after relatively minor surgeries [3,8]. They believed it reasonable to recognize that their patients might be within a subset of elderly people at risk for developing SIADH without other risk factors, and that a relatively minor surgical procedure might have increased their patients' susceptibility to the syndrome.…”
Section: Case Reportmentioning
confidence: 97%
“…Recently there have been reports of SIADH in patients undergoing minor surgeries, such as laparoscopic cholecystectomy, appendectomy, and cataract extraction under local anesthesia [2][3][4][5][6][7][8][9][10][11][12]. In terms of endoscopic treatment, no case of SIADH has been reported, although several reports have shown patients with hyponatremia after preparation for colonoscopy [17][18][19].…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Die postoperative Hyponatriämie durch eine inadäquate ADH-Freisetzung wurde nicht nur nach großen operativen Eingriffen, sondern auch nach minimal invasiven Operationen beobachtet [5]. Auch das Schädel-Hirn-Trauma kann eine inadäquate ADH-Sekretion induzieren.…”
Section: Syndrom Der Inappropriaten Adh-sekretionunclassified